2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7025297
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel correlation filters for human action recognition

Abstract: In this work, we propose to employ multi-channel correlation filters for recognizing human actions (e.g. waking, riding) in videos. In our framework, each action sequence is represented as a multi-channel signal (frames) and the goal is to learn a multi-channel filter for each action class that produces a set of desired outputs when correlated with training examples. The experiments on the Weizmann and UCF sport datasets demonstrate superior computational cost (real-time), memory efficiency and very competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Partial-aliasing correlation filters were introduced to optimise the performance by producing sharper correlation peaks [30]. Efficacy of CPR has also been exploited for human action recognition in some recent studies [31][32][33][34][35][36], where these filters have shown quite promising results.…”
Section: Latest Trends In Cpr Filtersmentioning
confidence: 99%
“…Partial-aliasing correlation filters were introduced to optimise the performance by producing sharper correlation peaks [30]. Efficacy of CPR has also been exploited for human action recognition in some recent studies [31][32][33][34][35][36], where these filters have shown quite promising results.…”
Section: Latest Trends In Cpr Filtersmentioning
confidence: 99%
“…Due to their efficiency and reasonable detection time, channel features quickly became a reference. Over the years, many extensions were proposed, in terms of either speed [13] or performance [11,5,52,24,28,54]. In all these works, the response of one filter region is summarized with one value, by averaging or subtracting means.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, individual filter responses would be more discriminative if characterized by more values. Moreover, since channel features were first introduced, heuristics [52,5,24,28] have been brought up to narrow down the filter search space. Therefore, in this paper, we propose to study the trade-off between these two factors and to show through the introduction of a new channel descriptor that several-valued filters can now reliably be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the process of identifying an authentic correlation shape can be used to refine the correlation outputs after the initial matching for improved discrimination. There are a large number of CFs that have been developed [1,2,3,4,5] for image matching problems and have been previously shown to perform well in biometric recognition scenarios like face [6], iris [7], periocular [8], fingerprint [9], and palm print [10]. However, the matching challenge is noticeably more difficult when only a single image is available for the gallery template, e.g., as in real-world applications (such as when matching crime-scene face images to face images in surveillance videos) and in several NIST biometric competitions [11,12,13] designed to mimic such real world scenarios.…”
Section: Introductionmentioning
confidence: 99%